The Short-Term Influences of Covid-19 Pandemic on Indonesia Stock Exchange - Syahfiraputri, Khairunnisa Nadhifah; Prasetiowati, Rr; Hersugondo, H (Jurnal Keuangan dan Perbankan, 2021)
This study aimed to discern the short-term influences of the Covid-19 pandemic on the Indonesia Stock Exchange. The stocks from nine industries in Indonesia Stock Exchange were putting to use in this study. In this study, the short-term cumulative abnormal return was calculated by applying the data taken from 59 days of trading after the confirmation notice of the first Covid-19 case in Indonesia. The result of the study depicted a Return in the event window (+1,+9) dropped drastically, which later bounced back; There was no cumulative abnormal return in the pre-event, and Cumulative abnormal return started to appear during event and post-event.DOI: 10.26905/jkdp.v25i3.5796